2022
DOI: 10.58258/jisip.v6i2.3151
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Permainan Olahraga Tradisional Terhadap Motivasi Belajar Dalam Pembelajaran Penjas Di Sekolah Dasar

Abstract: Penelitian ini berfokus pada olahraga tradisional sebagai alat untuk membantu proses pembelajaran penjas, olahraga tradisional pada dasarnya merupakan permainan rakyat pada jaman dahulu, kemudian banyak sekali manfaat dari permainan tradisional tersebut mulai dari aspek kognitif, afektif, dan psikomotorik, untuk itu tujuan penelitian ini adalah untuk mengetahui pengaruh permainan tradisional terhadap motivasi belajar siswa. Penelitian ini menggunakan metode experimental dengan One-Grup Prettest-posttest design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
0
0
2
Order By: Relevance
“…This current finding supported the previous studies which had revealed that parenting and motivation influenced students' learning outcomes. showed that parenting and schools' facilities had a significant influence towards students' learning intensity which directly affected their learning outcomes (Permana & Purnama, 2022). It was relevant to the study which showed that learning motivation had a role as intervening variables significantly influenced by parenting and other factors (Prabasari & Subowo, 2017;Rosida and Widiastuti., 2018).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This current finding supported the previous studies which had revealed that parenting and motivation influenced students' learning outcomes. showed that parenting and schools' facilities had a significant influence towards students' learning intensity which directly affected their learning outcomes (Permana & Purnama, 2022). It was relevant to the study which showed that learning motivation had a role as intervening variables significantly influenced by parenting and other factors (Prabasari & Subowo, 2017;Rosida and Widiastuti., 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Previous study state that education is a means used to improve human resources' quality in which the government and other stake holders continuously innovate the education system to improve its quality (Prabasari & Subowo, 2017). Education is also perceived as a way of improving nation's human resources in which it should be conducted optimally to build human resources who are competent and potential in this globalization era (Permana & Purnama, 2022;Rosida & Widiastuti, 2018). It is also argued that education has an important role in building an individual cognition, skill, and attitude as a better human resource (Farhan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Adapun item tes yang dilakukan antara lain: lari 40 meter, tes gantung siku tekuk, sit up 30 detik, loncat tegak dan lari 600 meter (Sepdanius, Sazeli, & Komaini, 2019) . Sedangkan untuk mengetahui motivasi peserta didik menggunakan angket motivasi dengan nilai validitas 0.748 dan reliabilitas 0.941 (Wardani, 2022). Data dianalisis dengan menggunakan uji independen sampel t tes menggunakan SPSS 24.…”
Section: Metodeunclassified
“…Hal ini di dukung oleh penelitan yang sudah dilakukan sebelum nya dapat di lihat dari tabel di atas bahwa permainan tradisional ini dapat membantu untuk 2023. Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga 7 (1): 54 -61 meningkatkan motivasi siswa dalam belajar khususnya pembelajaran penjas (Wardani, 2022). Permainan tradisional bentengan bentengan memberikan pengaruh yang positif terhadap motivasi belajar siswa dalam mengikuti pembelajaran lari sprint.…”
Section: Pembahasanunclassified